Pembentukan Karakter Pelajar Pancasila melalui Pembelajaran Batik pada Sekolah Lintas Etnis di Pekalongan - Suhail Kamal, Ahmad; Kafi, Faishal; Muyassaroh, Atin; Tapsirudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
One of the local content subjects in elementary schools in Pekalongan City is batik learning. Batik learning can be a means of instilling character in students. The cultural acculturation of three ethnic groups in Pekalongan City, namely Arab, Javanese, and Chinese (ARJATI) which researchers describe as Trimatra in Pekalongan City influences the patterns and motifs and colors of batik in the local area of ​​Pekalongan City. This study is a causal associative study using a non-probability sampling technique, namely purposive sampling. This study uses a quasi-experimental method with a one group pretest-posttest design. The subjects of this study were fifth grade elementary school students in Pekalongan City. Data analysis in this study was carried out using a paired t-test. The results of the t-test obtained obtained a sig. (2-tailed) value of 0.00 or <0.05, which means that there is a difference in the pretest and posttest values ​​after being given treatment. These results prove that out of 45 students who were sampled, there was a positive influence in batik learning with the Pancasila student profile. During the learning process, especially when practicing batik making, there is also a mutual cooperation behavior, upholding an attitude of tolerance, independence, and understanding batik as a local culture inherited from our ancestors.